Biografi Syekh Datuk Kota Bangun - Hasbi, Sakinah; Nasution, Abdul Gani Jamora; Almeida, Annisa; Harahap, Masbulan; Purba, Nadia Haviza (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article examines the history of the arrival of Islam to North Sumatra with a focus on the figure of Sheikh Datuk Kota Bangun. Through a biographical approach, this research aims to explore the contribution of Sheikh Datuk Kota Bangun in developing Islam in the region. The research gathered information from various sources, including Hikayat Hamparan Perak and related tombs. The problem formulation highlights the identification of this figure and his contribution, while the research objective is to provide an in-depth understanding of his role and impact in the development of Islam in North Sumatra. The research method uses a biographical approach by collecting data from historical documents, personal notes and archives. The research details his background, education and concrete contributions, while exploring the values reflected in North Sumatran society. Sheikh Datuk Kota Bangun, great cleric of North Sumatra, key to the spread of Islam, contributions include the establishment of mosques and Islamic educational institutions. Its influence on the city of Medan, especially in its formation by Guru Patimpus Sembiring Pelawi, is revealed. Research highlights its central role in the process of Islamization in the region. His grave is considered sacred, with mystical stories and miracles, strengthening the legend as the founder of the village. In conclusion, Sheikh Datuk Kota Bangun played a vital role in the spread of Islam in North Sumatra.